SAMHALLS RETUREMBALLAGE - En fallstudie av ojämn arbetsbelastning - Skoog, Lovisa; Bäckström, Robin (My University, 2018)
The essay studies the material flow in a function that works with return packaging at one subcontractor in Gothenburg´s automotive industry. The study maps and analyzes the material flows and duties that are bound to the function. The study has been conducted in the form of field studies at the factory and involved talks and interviews with the staff, also observations and flow measurements took place. The background to the study is that Samhall experienced problems with the resource allocation. The problem was characterized by unforeseen overload, resulting in strain work situation for the employees, and lower profitability. The study shows that the problem arises from both pushing and uneven flow design, which makes significant amount of workload accumulates between the production and the function. The workload subsequently reaches the function in a large amount without predictability, and causes an overload in the capacity of the function. The study shows that the problem can be addressed by partly reduce the accumulated workload in the system, mainly by introducing signaling system. The signal system should be introduced in the high storage and also in the transport of the pallets that collects boxes throughout the factory, so that they don’t stand full. The starting point for the improvement work is, however, that the function shapes a statistical base that describes the influx of the most significant articles.
Keywords: Produktion; Transport; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Sustainable Development; Other industrial engineering and economics